Understanding Behavior of Consumption Expenditure of Households - Mohd Bakri, Syazwani; Rambeli @ Ramli, Norimah; Hashim, Emilda; Mahdinezhad, Maryam; Abdul Jalil, Norasibah (International Business Education Journal, 2017)
There are two major trends in household financial level in Malaysia. The financial size level of households has expanded since 2002 so as the composition of household assets now are more wide-ranging. A study is carried out to identify the dominant factors that influence the household consumption expenditure in Malaysia between year 1970 to 2014. This study uses household income (YH) and inflation (CPI) as its independent variables, while using household consumption expenditure (C) as its the dependent variable. This study employs econometric method, namely Ordinary least squares (OLS) or linear least squares to determine variables that are significant and accurate. The result of this research shows that all tested variables influence household consumption expenditure in Malaysia. The result also suggests that, household income has positive and significant relationship with household consumption expenditure. Meanwhile, consumer price index, which represents inflation rate, negatively influences household consumption expenditure. To emphasize, Multiple Linear Regression model is the best model to estimate household consumption spending pattern in Malaysia.